Promosi Kesehatan Reproduksi Tema Pubertas di SMP Dharma Pancasila Medan 2025 - Zahara Ramadani; Dilla Ramadhani; Sari Nur Lyza; Kiki Anugrah; Nurhayati Nurhayati (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescence is a transitional period characterized by puberty, involving biological, psychological, and social changes toward adulthood. A lack of proper understanding of puberty may cause confusion and negative attitudes among adolescents, especially when reproductive health topics are still considered taboo. This community service activity aimed to improve adolescents’ understanding of puberty as a natural process and to foster positive attitudes and self-confidence in facing bodily changes. The activity was conducted on December 16, 2025, at SMP Dharma Pancasila Medan, involving eighth-grade students as participants. A descriptive qualitative approach was applied using participatory educational methods, including health education sessions, interactive discussions, ice-breaking activities, and quizzes. The results showed that participants were enthusiastic and actively engaged throughout the activity. Adolescents demonstrated improved understanding of puberty and reproductive health and felt more comfortable asking questions and discussing related topics. This activity indicates that communicative and adolescent-appropriate reproductive health promotion is effective in enhancing adolescents’ knowledge and positive attitudes toward puberty